Impact of Carrier Position and Surrounding Stiffness on Planet Carrier Bearing Loads. Issue 5 (September 2020) - Krause, A; Gnauert, J; Jacobs, G; Bosse, D
Abstract: Bearing failures in wind turbine gearboxes still occur which results in downtimes of wind turbines and hence increase the levelized costs of energy. One of these affected bearings is the generator sided planet carrier bearing as it is still subject to unexpected fatigue related failure modes. To reduce the occurrence of these failures a methodology is presented to determine the most influencing wind loads on this planet carrier bearing using the finite element method. Therefore a 1 MW wind turbine drive train model is used and the influence of several parameters influencing the load distribution of the bearing are investigated. These parameters are the surrounding stiffness of the bearing seat, the influence of the individual components of the wind loads and the circumferential position of the planet carrier. The results show that a realistic surrounding of the bearing seat leads to an unequal circumferential load distribution while the bearing itself is less loaded than using the generic surrounding of the bearing seat. The different components of the wind loads do not have much impact on the load distribution while the force acting on the rollers change. The different positions of the planet carrier also do not affect the circumferential load distribution.